Rancang Bangun dan Pembuatan Stand Target untuk Peningkatan Akurasi - Syamsul Arifin; Haffyandi, Recky Ahmad; Putra, Fadli Suardhana Eka; Anggara, Norma; Barikah, Amalia; Pratiwi, Endang; Rizal Ardiansyah (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2025)
A target is needed for kicks and attacks. Currently, these targets are always held by the lecturer, which, when used, significantly wastes time in learning sessions. With the funded Community Service Program (PKM) activity, the lecturer developed his creativity by creating a target stand, which was still incomplete at the time. The results of this community service implementation will impact students in the Physical Education Department at Lambung Mangkurat University. Lecturers teaching martial arts courses have greatly benefited from the presence of this target stand. Survey data analysis results are still in progress and will be attached to the final report. In this case, the partner is a colleague within the Physical Education Department, with whom he has a collaboration in the construction and welding fields. 80% of sports equipment is made from hard materials such as steel. Therefore, the Department has a long-standing partnership with DTK (Dita Teknik Kontruksi). Furthermore, metal sports equipment is regularly maintained, and if damaged, the partner is ready to repair it at a certain capacity.